Jeremie-Bonneau/Milne_Fiord_2011_2019_model: Milne_Fiord_2011_2019_model - Jeremie-Bonneau (Zenodo, 2021)
Model, input, output and ADCP data as used in Bonneau et al. 2021 J. Bonneau, B.E. Laval, D. Mueller, A.K. Hamilton, A.M. Friedrichs, A.L. Forrest. 2021. Winter Dynamics in an Epishelf Lake: Quantitative Mixing Estimates and Ice Shelf Basal Channel Considerations. Journal of Geophysical Research: Oceans